Chemotherapy-induced neutropenia elicits metastasis formation in mice by promoting proliferation of disseminated tumor cells - Massimo Russo; Nicolò Panini; Paola Fabbrizio; Laura Formenti; Riccardo Becchetti; Cristina Matteo; Marina Meroni; Claudia Nastasi; Andrea Cappelleri; Roberta Frapolli; Giovanni Nardo; Eugenio Scanziani; et al. (OncoImmunology, 2023)
Chemotherapy is the standard of care for most malignancies. Its tumor debulking effect in adjuvant or neoadjuvant settings is unquestionable, although secondary effects have been reported that paradoxically promote metastasis. Chemotherapy affects the hematopoietic precursors leading to myelosuppression, with neutropenia being the main hematological toxicity induced by cytotoxic therapy. We used renal and lung murine tumor models metastatic to the lung to study chemotherapy-induced neutropenia (CIN) in the metastatic process. Cyclophosphamide and doxorubicin, two myelosuppressive drugs, but not cisplatin, increased the burden of artificial metastases to the lung, by reducing neutrophils. This effect was recapitulated by treatment with anti-Ly6G, the selective antibody-mediated neutrophil depletion that unleashed the formation of lung metastases in both artificial and spontaneous metastasis settings. The increased cancer dissemination was reversed by granulocyte-colony stimulating factor-mediated boosting of neutrophils in combination with chemotherapy. CIN affected the early metastatic colonization of the lung, quite likely promoting the proliferation of tumor cells extravasated into the lung at 24–72 hours. CIN did not affect the late events of the metastatic process, with established metastasis to the lung, nor was there any effect on the release of cancer cells from the primary, whose growth was, in fact, somewhat inhibited. This work suggests a role of neutrophils associated to a common cancer treatment side effect and claims a deep dive into the relationship between chemotherapy-induced neutropenia and metastasis.